PENGARUH TERAPI SLOW STROKE BACK MASSAGE DENGAN MINYAK ESSENSIAL LAVENDER TERHADAP PENURUNAN INTENSITAS NYERI LOW BACK PAIN - Primayanthi, A.A.Ayu Emi; Azis, Abdul; Puspita, Luh Mira (Coping: Community of Publishing in Nursing; Vol 4 No 1 (2016): APRIL 2016, 2016)
Low Back Pain is pain that is felt in the lower back region. This pain can be local or radicular or both and felt among the bottom corner of the ribs to fold under the buttocks are in the lumbar region. Pain management is usually the pharmacological and non-pharmacological therapies. Cutaneous stimulation, distraction, relaxation, guided imagery, and hypnosis are examples of non-pharmacological interventions that are often used in nursing to manage pain, one of them with a slow-stroke back massage therapy combined with lavender essential oil. This study aims to determine the therapeutic effect of slow stroke back massage with lavender essential oil to decrease the intensity of pain in low back pain at Latu Usadha nursing clinics. This research uses a pre-experimental study using one group pre-test and post-test design without control conducted on 24 respondents selected by incidental sampling technique. Data collected by interview using VAS pain scale were performed before and after the intervention. Data using Shapiro Wilk normality test and then the data is processed by using the Wilcoxon test. Results obtained is ? = 0.000 means there is a therapeutic effect of slow stroke back massage with lavender essential oil to decrease pain in low back pain. Therapy SSBM with lavender oil can reduce pain in low back pain.
Keywords: Lavender Essential Oil, Low Back Pain, Slow Stroke Back Massage